A method of improving the dispersion of graphene nanoplatelets in cellulose acetate based composite. (30th May 2022) - Hu, Qipeng; Gu, Han; Wang, Chao; Ding, Yajun; Ying, Sanjiu
The application of cellulose acetate (CA) in various industrial areas is strongly influenced by thermal stability. Graphene nanoplatelets (GNPs) as a highly thermal conductive filler is a promising choice to modify the stability of CA, while the practical effect falls short of the expectations associated with the promise of individually dispersed graphene owing to poor dispersion. Supercritical carbon dioxide (SC-CO2 ) is favorable to nanoparticles dispersion. Thus, the method, introducing SC-CO2 into the CA/GNPs system during extrusion process, was proposed to modify GNPs dispersion in CA matrix. As three main process parameters, it was researched that the effects of injection flowrate, temperature and screw rotation-rate on GNPs dispersion in CA matrix. The dispersion quality of GNPs was enhanced with the rising of injection flowrate, and the average visible GNPs count of sample G1.25 C0.5 T37 R9 decreased 74.79%, compared with sample G1.25 C0.1 T37 R9 . The dispersion quality of GNPs was enhanced with the rising of temperature, and the average visible GNPs count of sample G1.25 C0.3 T41 R9 decreased 63.63%, compared with sample G1.25 C0.3 T33 R9 . The dispersion quality of GNPs decreased with the rising of screw rotation-rate, and the average visible GNPs count of sample G1.25 C0.3 T37 R5 decreased 77.71%, compared with sample G1.25 C0.3 T37 R13 . Thermogravimetric analysis revealed that a better GNPs dispersion is beneficial to CA stability even at an extremely low level. The maximum-weight-loss rate of the first weight-loss-stage of samples G1.25 C0.5 T37 R9, G1.25 C0.3 T41 R9 and G1.25 C0.3 T37 R5 appeared at 212, 224 and 225°C, while that of samples G1.25 C0.1 T37 R9, G1.25 C0.3 T33 R9 and G1.25 C0.3 T37 R13 appeared at 207, 219 and 219°C, with an increment of 5, 5 and 6°C, when the content of introduced GNPs is merely 1.25‰.